Antulla’s tomb and Martial’s: poetic closure in book 1 - Larash, Patricia (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The final seven epigrams of Martial’s Book 1 form a subtle but important closural sequence (epigrams 1.112-1.118 inclusive). Despite their great variatio of topics, the seven epigrams are linked through concerns about the boundary between life and death, the integrity of a monument, and the theme of dignus legi, or what makes someone “worthy of being read.” Through a series of close readings, this article argues for the coherence of this sequence on formal, thematic, and verbal grounds. The sequence is centered on a pair of epigrams on the kepotaphion or tomb-garden of a young girl named Antulla (1.114 and 1.116). The function of this closural sequence is both formal, to bring closure to a disparate collection of epigrams, and thematic, to reprise themes from the mock-epitaph with which Martial opens book 1 (1.1).